Treatment of the Fractional Curve of Adult Scoliosis With Circumferential Minimally Invasive Surgery Versus Traditional, Open Surgery: An Analysis of Surgical Outcomes. Issue 8 (December 2018) - Chou, Dean; Mummaneni, Praveen; Anand, Neel; Nunley, Pierce; La Marca, Frank; Fu, Kai-Ming; Fessler, Richard; Park, Paul; Wang, Michael; Than, Khoi; Nguyen, Stacie; Uribe, Juan; et al.
Study Design: Retrospective, multicenter review of adult scoliosis patients with minimum 2-year follow-up. Objective: Because the fractional curve (FC) of adult scoliosis can cause radiculopathy, we evaluated patients treated with either circumferential minimally invasive surgery (cMIS) or open surgery. Methods: A multicenter retrospective adult deformity review was performed. Patients included: age >18 years with FC >10°, ≥3 levels of instrumentation, 2-year follow-up, and one of the following: coronal Cobb angle (CCA) > 20°, pelvic incidence and lumbar lordosis (PI-LL) > 10°, pelvic tilt (PT) > 20°, and sagittal vertical axis (SVA) > 5 cm. Results: The FC was treated in 118 patients, 79 open and 39 cMIS. The FCs had similar coronal Cobb angles preoperative (17° cMIS, 19.6° open) and postoperative (7° cMIS, 8.1° open), but open had more levels treated (12.1 vs 5.7). cMIS patients had greater reduction in VAS leg (6.4 to 1.8) than open (4.3 to 2.5). With propensity matching 40 patients for levels treated (cMIS: 6.6 levels, N = 20; open: 7.3 levels, N = 20), both groups had similar FC correction (18° in both preoperative, 6.9° in cMIS and 8.5° postoperative). Open had more posterior decompressions (80% vs 22.2%, P < .001). Both groups had similar preoperative (Visual Analogue Scale [VAS] leg 6.1 cMIS and 5.4 open) and postoperative (VAS leg 1.6 cMIS and 3.1 open) leg pain. All cMIS patients had interbody grafts; 35% of open did. There was no difference in change of primary CCA, PI-LL, LL, Oswestry Disability Index, or VAS Back. Conclusion: Patients' FCs treated with cMIS had comparable reduction of leg pain compared with those treated with open surgery, despite significantly fewer cMIS patients undergoing direct decompression.